In vitro anti-angiogenic effects of Hemidesmus indicus in hypoxic and normoxic conditions. (13th March 2015) - Turrini, E.; Ferruzzi, L.; Guerrini, A.; Gotti, R.; Tacchini, M.; Teti, G.; Falconi, M.; Hrelia, P.; Fimognari, C.
Abstract: Ethnopharmacological relevance: The decoction of the roots of Hemidesmus indicus is widely used in the Indian traditional medicine for many purposes and poly-herbal preparations containing Hemidesmus are often used by traditional medical practitioners for the treatment of cancer. In the context of anticancer pharmacology, anti-angiogenic therapy has become an effective strategy for inhibiting new vessel formation and contrast tumor growth. These considerations are supported by the evidence that most tumors originate in hypoxic conditions and limitation of oxygen diffusion stimulates the formation of tumor abnormal microvasculature. Aim of this study was to evaluate the in vitro anti-angiogenic potential of Hemidesmus indicus (0.31–0.93 mg/mL) on human umbilical vein endothelial cells and delineate the main molecular mechanisms involved in its anti-angiogenic activity both in normoxia and hypoxia. Materials and methods: The decoction of Hemidesmus indicus was subjected to an extensive HPLC phytochemical characterization. Its in vitro anti-angiogenic potential was investigated in normoxia and hypoxia. Cell proliferation, apoptosis induction, and inhibition of endothelial cell migration and invasion were analyzed by flow cytometry. The endothelial tube formation assay was evaluated in matrix gel. The capillary tube branch points formed were counted using a Motic AE21 microscope and a VisiCam videocamera. The regulation of key factors of the neovascularization process such as VEGF, HIF-1α and VEGFR-2 was explored at mRNA and protein level by real time PCR and flow cytometry, respectively. Results: Treatment with Hemidesmus resulted in a significant inhibition of cell proliferation and tube formation in both normoxia and hypoxia. Hemidesmus differently regulated multiple molecular targets related to angiogenesis according to oxygen availability. In normoxia, the inhibition of VEGF was the main responsible for its anti-angiogenic effect; the angiogenesis inhibition induced in hypoxia was regulated by a more complex mechanism involving firstly HIF-1α inhibition, and then VEGF and VEGFR-2 down-regulation. Additionally, the inhibition of endothelial cell migration and invasion by Hemidesmus was more pronounced in normoxia than in hypoxia, possibly due to the physiological enhanced induction of invasion characteristic of hypoxia. Conclusions: Our results indicate that Hemidesmus might represent a promising therapeutic strategy for diseases in which the inhibition of angiogenesis could be beneficial, such as cancer. The antiangiogenic activity of Hemidesmus is based on multiple interactions with critical steps in the angiogenic cascade. VEGF expression stimulated by HIF-1α as well as endothelial cell migration and differentiation represent important targets of Hemidesmus action and might contribute to its cancer therapeutic efficacy that is presently emerging and offer a scientific basis for its use in traditional medicine. Graphical abstract: